Evaluation of compressive strength for paper sludge brick - Mohammad Rizam Che Beson (School of Environmental Engineering , University Malaysia Perlis, 2010)
The main objectives of this research are to evaluate the physical properties compressive strength and water absorption, of brick containing paper sludge following Standard Specification for Building Works 2005 JKR, to determine effect of using paper sludge as brick mixes and to compare the result with common sand brick.